Regional Interest Rate Variations: Evidence from the Indonesian Credit Markets - Masagus M. Ridhwan; Henri L.F. de Groot; Piet Rietveld; Peter Nijkamp (Tinbergen Institute, 2012)
This paper explores the determinants of regional differences in interest rates based on a simple theoretical model of loan pricing. The model demonstrates how risks, costs, market concentration and scale economies jointly determine the bank's interest rates. Using recent data of the Indonesian local credit markets, we find that regional interest rate variations are positive and significantly affected by the banks' risk factor, the operating costs, and market concentration. Scale economies negatively affect the interest rates. These findings help to explain geographical segmentation in loan markets.
urn:NBN:nl:ui:31-1871/38510
Keywords: R51; E43; C33; 330; regional capital mobility; loan pricing; interest rates; Indonesia; Kreditgeschäft; Zins; Kapitalmobilität; Skalenertrag; Kreditmarkt; Marktsegmentierung; Indonesien